Improving productive performance, immunity, and health status of growing rabbits by using honey bee venom (Apis mellifera) - Elkomy, Alaa E.; Sadaka, Tarek A.; Hassan, Saber S.; Shawky, Omnia; El-Speiy, Mohamed E.; El-Beshkar, Mohamed; Wadaan, Mohammad A. M.; El-Tahan, Hatem M.; Cho, Sungbo; Kim, In Ho; El-Tahan, Hossam M. (Frontiers in Veterinary Science, 2023)
To investigate the effect of bee venom (BV) as a natural growth promotor on growing rabbits as an alternative to antibiotics, sixty 35-day-old Californian male rabbits with an average body weight of 584±9 gm were randomly divided into five equal groups as follows:The 2 nd , 3 rd , 4 th and 5 th group received drinking water supplied with 10 mg Oxytetracycline (OXT) or 2, 4 and 8 mg bee venom (BV) /kg body weight/day; while the first group served as a control group. The 2 nd group received drinking water supplied with 10 mg Oxytetracycline (OXT), while the 3 rd , 4 th , and 5 th groups received 2, 4 and 8 mg bee venom (BV) /kg body weight/day in drinking water, and the first group was served as a control group. The growth performance features were positively impacted by adding BV (P≤0.01) compared to the control, whereas LBW and BWG increased and FI reduced. Significantly improved carcass characteristics (P≤0.01) as a result of the BV supplementation. Blood characteristics showed a significant reduction (P≤0.01) in liver enzyme activities and Cholesterol, Triglycerides, and Low-density lipoproteins Cholesterol (LDL) as affected by BV treatment; inversely, total protein and globulin were significantly increased (P≤0.01). Similarly, BV had a positive effect (P≤0.01) on anti-oxidant status (Total anti-oxidant capacity (TAC), Glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT)). In contrast, the lipid peroxidation biomarker (Malondialdehyde (MDA)) was significantly decreased. The immunoglobulin (IgG and IgM) was significantly increased (P≤0.01) by BV treatment. There was a positive effect of low BV levels on decreasing both cecum TBC and pathogenic bacterial count (Salmonella spp., E.coli spp., Proteus spp., and Clostridia spp.) that was significant (P≤0.01). In conclusion, BV can be a natural growth promoter to enhance growth performance traits, immunological and anti-oxidative responses, and reduce pathogenic bacteria in the hindgut of growing rabbits.